2022
DOI: 10.1177/08927057221124480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weld-line on tensile properties for thermoplastic glass filled material

Abstract: In an injection molding process, a weld-line forms when two flow fronts meet each other. Weld-line is a weak area which reduces the strength of the part locally. For multiple gate and complex part, molding weld-lines are unavoidable, therefore mechanical behavior of the weld-line needs to be predicted. This paper presents the effect of weld-lines on tensile properties of glass fibers reinforced polyamide-6 composite. An injection molding plaque tool has been designed and manufactured with the inputs from mold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Equation ( 10) further used to introduce weld-line strength as a function of reptation time under isothermal conditions by Kausch and Tirrell 38 and validated molecular dynamics and experimental work. The weld-line strength factor is defined in Equation (11).…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation ( 10) further used to introduce weld-line strength as a function of reptation time under isothermal conditions by Kausch and Tirrell 38 and validated molecular dynamics and experimental work. The weld-line strength factor is defined in Equation (11).…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Weld-line, also known as the knit line, is a flaw that occurs in injection molding when two or more polymetric melt-fronts are meeting each other. 1,10,11 When the rounded flow fronts of the melt streams come into contact with each other, they flatten, and fuse as shown in Figure 1. Stretching of the very viscous flow fronts is required in this operation.…”
mentioning
confidence: 99%
“…Such particles have a high influence on weld-line effects, as they are much bigger than the polymer molecules and do not merge when colliding in a melt front, and orientate almost parallel to the weld line. [14,25,29,30] Therefore, the aim of this work was to investigate the influence of injection molding processing parameters on the mechanical properties of specimens, with and without weld lines, of reinforced and unreinforced polypropylene. The results from the five different polypropylene grades were related to their melt flow indexes to find a connection between weld-line effects and melt flow indexes.…”
Section: Introductionmentioning
confidence: 99%
“…Such particles have a high influence on weld‐line effects, as they are much bigger than the polymer molecules and do not merge when colliding in a melt front, and orientate almost parallel to the weld line. [ 14,25,29,30 ]…”
Section: Introductionmentioning
confidence: 99%
“…Weng et al, 7 carried out a series of injection molding experiments and constructed a simulation model to evaluate the filling quality of micropillars by varying packing pressure and melt temperature and concluded that the filling quality of microstructures of the micropillars can be improved with increasing melt temperature and packing pressure. Jadhav et al 11 conducted an experimental investigation to find the effect of weld-line and weld-line angle on tensile properties for thermoplastic glass-filled material and found a 49% strength reduction in weld-line specimens compared with those without weld-line specimens. Gao et al 12 developed a new simulation method based on healing theory and the interdiffusion model for the prediction of product strength considering weld-line and fiber orientation and concluded that their approach is effective as far as design aspects are concerned.…”
Section: Introductionmentioning
confidence: 99%